SPECTRUM OF PROBLEMS AND MOTIVES IN VASYL PORTIAK’S SHORT STORIES - Protsiuk, L. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Article analyses the main problems and motives of Vasyl Portiak’s short stories. This author’s works belong to the most refined examples in the Ukrainian literature.